Variation in triggers and use of perioperative blood transfusion in major gastrointestinal surgery. Issue 11 (5th August 2014) - Ejaz, A; Spolverato, G; Kim, Y; Frank, S M; Pawlik, T M
Abstract: Background: The decision to perform intraoperative blood transfusion is subject to a variety of clinical and laboratory factors. This study examined variation in haemoglobin (Hb) triggers and overall utilization of intraoperative blood transfusion, as well the impact of transfusion on perioperative outcomes. Methods: The study included all patients who underwent pancreatic, hepatic or colorectal resection between 2010 and 2013 at Johns Hopkins Hospital, Baltimore, Maryland. Data on Hb levels that triggered an intraoperative or postoperative transfusion and overall perioperative blood utilization were obtained and analysed. Results: Intraoperative transfusion was employed in 437 (15·6 per cent) of the 2806 patients identified. Older patients (odds ratio (OR) 1·68), patients with multiple co-morbidities (Charlson co-morbidity score 4 or above; OR 1·66) and those with a lower preoperative Hb level (OR 4·95) were at increased risk of intraoperative blood transfusion (all P < 0·001). The Hb level employed to trigger transfusion varied by sex, race and service (all P < 0·001). A total of 105 patients (24·0 per cent of patients transfused) had an intraoperative transfusion with a liberal Hb trigger (10 g/dl or more); the majority of these patients (78; 74·3 per cent) did not require any additional postoperative transfusion. Patients who received an intraoperative transfusion were at greater risk of perioperative complications (OR 1·55; P = 0·002), although patients transfused with a restrictive Hb trigger (less than 10 g/dl) showed no increased risk of perioperative morbidity compared with those transfused with a liberal Hb trigger (OR 1·22; P = 0·514). Conclusion: Use of perioperative blood transfusion varies among surgeons and type of operation. Nearly one in four patients received a blood transfusion with a liberal intraoperative transfusion Hb trigger of 10 g/dl or more. Intraoperative blood transfusion was associated with higher risk of perioperative morbidity. Abstract : Overuse of blood needs